A Green Approach to Synthesize Dihydropyrimidinone Derivatives by Using Anhydrous ZnCl2 Catalyst Under Refluxing Condition in Heptane-Toluene Medium via Biginelli Reaction - Akhter, Kawsari; Jahan, Khorshada; Romman, U.K.R.; Giasuddin Ahmed, M.; Sharifur Rahman, Md.; Al-Amin, Md. (Asian Journal of Chemistry, 2015)
Aldehydes, 1a-g (1a, Ar = 4-Cl-C6H4, 1b, Ar = 4-CH3-C6H4, 1c, Ar = 2-Cl-C6H4, 1d, Ar = 2-CH3- C6H4, 1e, Ar = -C6H5, Ar = 4-Cl-C6H4, 1g, Ar = 2-Cl-C6H4) reacted with acetylacetone 2a and urea/thiourea 3a-b in the presence of anhydrous zinc chloride under refluxing condition in heptane-toluene medium to give the corresponding 5-aceto-4-aryl-6-methyl-2-oxo-1,2,3,4-tetrahydropyridimidine 4a-d and 5-aceto-4-aryl-6-methyl-2-thio-1,2,3,4-tetrahydropyridimidine 4e-g. The structure of the compounds 4a-g were confirmed by their UV, IR, 1H NMR and 13C NMR analysis.